Instagram as a network of promotion and hypermediation of rural tourism: the case of Aldeias Historicas - Martinez-Rolan, X.; Tymoshchuk, O.; Pinero-Otero, T.; Reno, D. [UNESP] (Laboratorio Tecnologias Informacion & Nuevos Analisis Comunicacion Social, 2019)
Changes in the media ecosystem have led to transformations in communication languages, now in imaginary spaces like Instagram, even strengthening the hypermediation provided by social networks. The article presents a metric research on the use of the Instragram by the Portuguese initiative Aldeias Historicas in search of tourism promotion in the region. For the investigation, the InstaBro tool has been adopted, which offered information for a quantitative analysis, but also a qualitative interpretation. The results offer information about the importance of hypermediation in rural tourism promotion processes through digital communication
Keywords: Communication; media ecology; social media; rural tourism; Instagram; hypermediation